Creativity: Influencing Factors on Student Innovation and Creativity Skills in the Design of Industrial Products - Songwut Egwutvongsa (My University, 2023)
The objective of this research was to study the influencing factors related to the creativity and innovation skills of students in the field of industrial product design, and the population was defined as three hundred and nine students in the product design program at King Mongkut’s Institute of Technology Ladkrabang with the sample group comprising two hundred and seventy-five 1st–4th year students selected using stratified sampling. Additionally, structured interviews were used as the research tool (Cronbach’s alpha = 0.803), which was analyzed by Exploratory Factor Analysis and Confirmatory Factor Analysis. In this case, it was found from the EFA analysis that there were three components (KMO = 0.950): 1) the fundamental component of self-concept, 2) the consideration of the impact on others, and 3) the drive component that stimulates development, with the goodness of fit index as follows: χ^2 = 22.202, df = 26, relative χ^(2 )= .854, p-value = .678, RMSEA = .000, RMR = .010, GFI = .985, AGFI = .963, NFI = .994, TLI = 1.002, PGFI = .388, RFI = .987, AIC = 102.202. In this study, the composition from EFA was shown to be consistent with the CFA by having a structural equation model with a measurement model that fits well with the theoretical model of stimulating creativity and innovation. Moreover, it corresponds to the empirical data at a good level with the following values: χ^(2 )= 19.964, relative χ^(2 )= .768, p-value = .795, RMSEA = .000, GFI = .987, CFI = 1.000.

Received: 9 February 2023 / Accepted: 20 April 2023 / Published: 5 May 2023
Keywords: Goodness of fit; Exploratory factor analysis; Impulse Buying and Technology Impacts